Economic determinants of intellectual property development in Ukraine - Schwodiauer, Gerhard; Maslak, M. V. (My University, 2021)
A detailed analysis of the negative trends in the development of intellectual property has been carried out, which create significant risks for Ukraine to lag behind technological leaders, reduce the independence and competitiveness of the economy, and devalue domestic investments in science and technology. The main ways of commercialization of intellectual property are determined: the use of intellectual property rights in one's own production; the introduction of rights to objects of intellectual property rights in the authorized capital of the enterprise; transfer (sale) of intellectual property rights. Emphasis is placed on the need to use as an objective criterion for determining the market value of an intellectual property object using the economic effect that the user of this property expects to receive within a certain period of time.
Економічні детермінанти розвитку інтелектуальної власності в Україні
Keywords: intellectual power; intangible assets; industrial power objects; commercialization